2010
DOI: 10.1007/s10800-009-0060-7
|View full text |Cite
|
Sign up to set email alerts
|

Bentonite electrical conductivity: a model based on series–parallel transport

Abstract: Bentonite has significant applications nowadays, among them as landfill liners, in concrete industry as a repairing material, and as drilling mud in oil well construction. The application of an electric field to such perimeters is under wide discussion, and subject of many studies. However, to understand the behaviour of such an expansive and plastic material under the influence of an electric field, the perception of its electrical properties is essential. This work serves to compare existing data of such ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…These evidences prompted the development of a specific non-linear conductivity model in geophysics called the 'three layers resistor model' by Wyllie & Southwick (1954). The three layers resistor model has since being extensively used and discussed in the literature (Sauer et al 1955;Spiegler et al 1956;Gast 1966;Bussian 1983;Mitchell 1993;Lima et al 2010) and extended to partially saturated media by Rhoades et al (1989) and Revil et al (2018a). Fig.…”
Section: O L U M E Av E R a G I N G T H E O Rymentioning
confidence: 99%
“…These evidences prompted the development of a specific non-linear conductivity model in geophysics called the 'three layers resistor model' by Wyllie & Southwick (1954). The three layers resistor model has since being extensively used and discussed in the literature (Sauer et al 1955;Spiegler et al 1956;Gast 1966;Bussian 1983;Mitchell 1993;Lima et al 2010) and extended to partially saturated media by Rhoades et al (1989) and Revil et al (2018a). Fig.…”
Section: O L U M E Av E R a G I N G T H E O Rymentioning
confidence: 99%
“…It should be observed that in literature there is a wide variety of works giving results that could be potentially useful for tackling the problem [3][4][5][6][7][8][9][10][11]. To the best of our knowledge, no specific studies are available for the considered problem.…”
Section: Introductionmentioning
confidence: 99%
“…This approach can be considered a classical one. Even if a specific sensor for the considered problem has not been presented in the literature, several studies in this field could suggest that this approach could be the most applicable to the problem [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The permittivity and conductivity of clay suspensions have been investigated by numerous authors [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. In a previous article [15], we have investigated both the electrophoretic mobility and the dielectric spectroscopy response of dilute montmorillonite particle suspensions of montmorillonite (0.1% volume fraction).…”
Section: Introductionmentioning
confidence: 99%